BIAK LANGUAGE: TRACE BACK - Martha Betaubun; Adolfina Krisifu; Ranta Butarbutar (Universitas Muhammadiyah Makassar, 2019)
This paper was conducted by literature research which is, firstly, aimed to describe the spread of Biak language as a lingua franca in the past in relation to its classification, users, domains, concurrent languages, internal varieties, spoken tradition and standardisation as well as the typology of the language. The language has been developed by its speakers throughout the bird’s head peninsula of West Papua. Secondly, it intended to trace “who (ancestors) and where” the language has been used. It is believed that language provides clues to investigate the ancestors and the spread of a race.